The assessment and improvement of the health status of vulnerable and low income individuals in South Africa: an analysis using quantitative and experimental methods - Rossouw, Laura (Stellenbosch : Stellenbosch University, 2016)
Thesis (DCom)--Stellenbosch University, 2016.